Polymerase chain reaction-based detection of minimal residual disease in multiple myeloma patients receiving allogeneic stem cell transplantation - G Martinelli; C Terragna; E Zamagni; S Ronconi; P Tosi; R Lemoli; G Bandini; N Testoni; M Amabile; E Ottaviani; S Buonamici; S Soverini; et al. (Haematologica, 2000)
BACKGROUND AND OBJECTIVES: Recent advances in the treatment of multiple myeloma (MM) include use of high-dose chemoradiotherapy followed by allografting. Although allografting with bone marrow (BM) or peripheral blood stem cells (PBSC) seems to improve clinical outcome and lengthen survival, only about 50% of patients reach stringently defined complete remission (CR), and most subsequently relapse. We assessed the clinical relevance of minimal residual disease (MRD) in 14 MM patients in CR after allografting with PBSC (6 patients) or BM (8 patients). DESIGN AND METHODS: Among the 30 out of 72 MM patients in our Institute who achieved CR after allografting, 14 had a molecular marker suitable for allo-specific polymerase chain reaction (PCR) analysis.Stringent molecular monitoring was done using clonal markers based upon rearranged immunoglobulin heavy-chain genes. Molecular remission (MCR) was defined as two consecutive negative PCR results. RESULTS: Seven of 14 (50%) molecularly monitored patients, achieved MCR and did not relapse after a median molecular follow-up of 60 months (range 36-120). Median time to obtain first PCR negativity was 12 (BM group) and 6 months (PBSC group), respectively. Of the seven patients (50%) who never achieved MCR, one relapsed. INTERPRETATION AND CONCLUSIONS: In conclusion, 50% of the MM patients in CR studied by us also achieved stringently-defined MCR. MCR was associated with a very low rate of clinical relapse.